Rooftop Urban Agriculture - Orsini, Francesco, editor 653835; Dubbeling, Marielle, editor 589790; Zeeuw, Henk de, editor 589792; Gianquinto, Giorgio, editor 653836 (Cham, Switzerland : Springer Nature, 2017)
This book guides architects, landscape designers, urban planners, agronomists and society on the implementation of sustainable rooftop farming projects. The interdisciplinary team of authors involved stresses the different approaches and the multi-faceted forms that rooftop farming may assume in any context. While rooftop farming experiences are sprouting all over the world the need for scientific evidence on the most suitable growing solutions, policies and potential benefits emerges. This volume brings together existing experiences as well as suggestions for planning future sustainable cities.